Analyses of the internal transcribed rDNA spacers (ITS1 and ITS2) of Indian weevils of Odoiporus longicollis (Olivier) reveal gene flow between locations. (28th December 2018) - Kumar, Lalitha Sunil; Shankar, Pallavi; Kulkarni, Vishvas M.
Abstract: An important step towards developing a successful integrated pest management (IPM) programme for the control of banana pseudostem weevil, Odoiporus longicollis (Olivier), a serious pest of banana in India, is the study of the population structure of the pest. In the present study, the genetic variation among 30 individual weevils of O.longicollis collected from six different locations was assessed by analysing the primary nucleotide sequences of the rDNA ITS1 and ITS2 regions. AMOVA, Mantel test, and the maximum likelihood trees of the haplotypes failed to reveal any phylogeographic structuring, which was confirmed by haplotype analysis and genetic differentiation estimates. The results indicate that the locations are not differentiated, i.e. there is gene flow between the locations. The star-shaped networks revealed a signature of demographic expansion that was confirmed by the different demographic tests. These results provide important information, which is essential for the development of suitable strategies for the control of this banana pest, as well as management of its resistance to insecticides.